2014
DOI: 10.1155/2014/905129
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Corneal Biomechanical Properties and Intraocular Pressure in Myopic Spanish Healthy Population

Abstract: Purpose. To examine biomechanical parameters of the cornea in myopic eyes and their relationship with the degree of myopia in a western healthy population. Methods. Corneal hysteresis (CH), corneal resistance factor (CRF), Goldmann correlated intraocular pressure (IOP), and corneal compensated IOP (IOPcc) were measured using the ocular response analyzer (ORA) in 312 eyes of 177 Spanish subjects aged between 20 and 56 years. Refraction was expressed as spherical equivalent (SE), which ranged from 0 to −16.50 di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
30
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 31 publications
3
30
2
Order By: Relevance
“…Corneal hysteresis (CH) and corneal resistance factor (CRF) are strongly correlated with CCT [46]. A relation between refractive error and corneal biomechanical properties has also been reported [7]. The relationship between other anterior segment parameters such as corneal curvature (CC), corneal astigmatism (CA), corneal volume (CV), mean keratometric ( K ) value, and corneal biomechanical properties has been also investigated and the results are controversial [811].…”
Section: Introductionmentioning
confidence: 99%
“…Corneal hysteresis (CH) and corneal resistance factor (CRF) are strongly correlated with CCT [46]. A relation between refractive error and corneal biomechanical properties has also been reported [7]. The relationship between other anterior segment parameters such as corneal curvature (CC), corneal astigmatism (CA), corneal volume (CV), mean keratometric ( K ) value, and corneal biomechanical properties has been also investigated and the results are controversial [811].…”
Section: Introductionmentioning
confidence: 99%
“…Its worldwide prevalence is over 22% of the current world population and is rising dramatically yearly, reaching 80% in certain Asian countries [ 1 , 2 ]. Several studies have revealed the correlation between the corneal biomechanical characteristics and myopic degree in children [ 3 ] and adult population [ 4 ]; nevertheless, the results are still lacking consistence in terms of the biomechanical parameters investigated [ 3 5 ]. Although axial length and corneal curvature have been shown to associate with refractive error, the relationship between the two parameters and corneal biomechanical behavior has not been clarified yet [ 3 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Corneal hysteresis (CH) and corneal resistance factor (CRF) are the main biomechanical parameters for evaluating the corneal viscoelasticity [ 8 ]. Several studies have reported that CH was significantly lower in patients with high myopia, and a relationship between the refractive error and corneal biomechanical properties has also been addressed in adult Spanish and Caucasian population [ 4 , 9 ]. However, this association failed to show in the study on Singaporean children [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies showed that CH and CRF significantly decreased with age in healthy population [ 38 , 39 ]. Other authors, however, demonstrated no correlation between corneal biomechanics and age by ORA [ 40 ]. With CorVis ST, Valbon et al reported that only the HC-time correlated significantly with age in healthy eyes [ 23 ].…”
Section: Discussionmentioning
confidence: 99%